Essential concepts in sociology - Giddens, Anthony; Sutton, Philip W. (Polity, 2017)
"Social life is in a constant process of change, and sociology cannot afford to stand still. Sociology today is theoretically diverse, covers a huge range of subjects and draws on a broad array of research methods. Central to this endeavour is the use of core concepts and ideas which allow sociologists to make sense of societies, though our understanding of these concepts is constantly evolving and changing. This clear and jargon-free book introduces a careful selection of essential concepts that have helped to shape sociology, and others that continue to do so. Going beyond brief, dictionary-style definitions, Anthony Giddens and Philip W. Sutton provide an extended discussion of each concept which sets it into historical and theoretical context, explores its main meanings in use, introduces some relevant criticisms, and points readers to its ongoing development in contemporary research and theorizing. Organized in ten thematic sections, the book offers a portrait of sociology through its essential concepts ranging from capitalism, identity and deviance to citizenship, the environment and intersectionality. It will be essential reading for all those new to sociology, as well as those seeking a reliable route map for a rapidly changing world"--Provided by publisher.